Pre-service teachers undertaking classroom research: developing reflection and enquiry skills - Medwell, Jane; Wray, David (Taylor & Francis, 2014)
This paper reports on the development of reflectiveness and research skills in eight preservice teachers, through their participation in a funded research project to develop the handwriting of children with literacy problems. The project aimed to analyse the reflections of the trainee teachers participating in an authentic research study and to consider what this reflection on practice might offer to the education of teachers in the current UK training context. The context for the paper was a project which engaged pre-service trainee teachers in researching the proposition that automaticity in handwriting plays a role in facilitating composing processes and that the automaticity of early writers can be trained. Some outcomes of the project for pupils are reported. Of the 39 children targeted in the project, 32 made significant progress in their performance on the handwriting automaticity test. The focus in the present paper is, however, on the participating trainee teachers and the paper suggests that conducting research was a significant learning event for these pre-service teachers and that, through working together, they were able to analyse their development as researchers and their learning during the research process. At a time when the English government views teacher training as a method of school improvement and the effectiveness of training is measured through its immediate impact on pupil outcomes, this study offers an example of how shared research can offer positive learning outcomes for pupils, develop the reflective thinking of pre-service teachers through researching a real problem, and develop links across a range of school and university settings